Genotypic Variation of Nitrogen Use Efficiency and Amino Acid Metabolism in Barley - Decouard, Bérengère; Bailly, Marlène; Rigault, Martine; Marmagne, Anne; Arkoun, Mustapha; Soulay, Fabienne; Caïus, José; Paysant-Le Roux, Christine; Louahlia, Said; Jacquard, Cédric; Esmaeel, Qassim; Chardon, Fabien; et al. (Frontiers in Plant Science, 2022)
Owing to the large genetic diversity of barley and its resilience under harsh environments, this crop is of great value for agro-ecological transition and the need for reduction of nitrogen fertilizers inputs. In the present work, we investigated the diversity of a North African barley genotype collection in terms of growth under limiting N (LN) or ample N (HN) supply and in terms of physiological traits including amino acid content in young seedlings. We identified a Moroccan variety, Laanaceur, accumulating five times more lysine in its leaves than the others under both N nutritional regimes. Physiological characterization of the barley collection showed the genetic diversity of barley adaptation strategies to LN and highlighted a genotype x environment interaction. In all genotypes, N limitation resulted in global biomass reduction, an increase in C concentration and a higher resource allocation to the roots, indicating that this organ undergoes important adaptive metabolic activity. The most important diversity concerned leaf nitrogen use efficiency (LNUE), root nitrogen use efficiency (RNUE), root nitrogen uptake efficiency (RNUpE) and leaf nitrogen uptake efficiency (LNUpE). Using LNUE as a target trait reflecting barley capacity to deal with N limitation, this trait was positively correlated with plant nitrogen uptake efficiency (PNUpE) and RNUpE. Based on the LNUE trait, we determined three classes showing high, moderate or low tolerance to N limitation. The transcriptomic approach showed that signaling, ionic transport, immunity, and response to stress were the major functions affected by N supply. A candidate gene encoding the HvNRT2.10 transporter was commonly up-regulated under LN in the three barley genotypes investigated. Genes encoding key enzymes required for lysine biosynthesis in plants, dihydrodipicolinate synthase (DHPS) and the catabolic enzyme, the bifunctional Lys-ketoglutarate reductase/saccharopine dehydrogenase are up-regulated in Laanaceur and likely account for hyperaccumulation of lysine in this genotype. Our work provides key physiological markers of North African barley response to low N availability in the early developmental stages.